Shared Control Based on an Ecological Feedforward and a Driver Model Based Feedback. Issue 5 (2019) - Pano, Béatrice; Zhao, Yishen; Chevrel, Philippe; Claveau, Fabien; Mars, Franck
Abstract: Haptic shared control is a consistent way to design an assistance for the lateral control of a vehicle. The most important problem raised by haptic shared control is to minimize useless conflicts between the driver and the assistance. To deal with, this paper proceeds in two stages. The first is concerned with feedforward synthesis in a new way, by identifying mainly the geometric part of driving from real driver data. The torque to apply to the steering wheel and more generally the reference trajectory is thus obtained from a second order model fed by the road curvature. Then, the feedback is designed based on a driver-vehicle-road model, using a mixed H2 /H ∞ control synthesis involving both lane following performance and sharing capabilities indicators. Finally, the shared control strategy is simulated on Matlab/Simulink using a vehicle-road model. The results obtained show good features both in terms of lane following and sharing performances. This control strategy seems then to be an interesting candidate for haptic shared control.